Polyoxometalate Cluster [V12b18o60h 6 Functionalized with the Copper(Ii) Bis-Ethylenediamine Complex - Venegas-Yazigi, D; Venegas-Yazigi, D (2011)
Three compounds based on the polyoxometalate building block [V 12B18O60H6], (Na) 10[(H2O)V12B18O60H 6]·18H2O (1), Na8[Cu(en) 2]2[V12B18O60H 6](NO3)2·14.7H2O (2), Na 7[Cu(en)2]2[V12B18O 60H6](NO3)·15.5H2O (3), (en = ethylenediamine), have been hydrothermally synthesized and characterized by single-crystal X-ray diffraction analysis and TGA. Compound 1 consists of polyoxovanadium borate [V12B18O60H6] clusters which are surrounded by sodium countercations in octahedral sites, stabilized by electrostatic interactions with the oxygen atoms of both vanadium and boron centres. However, compounds 2 and 3 correspond to more complicated structures, constructed from the same polyoxometalate clusters, which are interconnected by [Cu(en)2]2+ moieties via the terminal oxygen atoms of the polyoxoanions, generating one-dimensional structures. The functionalization of this polyoxovanadium borate cluster has been obtained by the use of [Cu(en)2]2+ complex ions, thus demonstrating the capacity of the terminal oxygen atoms of the cluster to bind transition metal centres. The structural stability of the [V12B 18O60H6] cluster permits the formation of functionalized polyoxometalate clusters, generating various crystalline lattices. © 2010 Elsevier B.V. All rights reserved.